The correlation of numerical ability with learning outcomes in mathematics economics of management students of the Universitas Sumatera Barat - Syahrial, Syahrial; Hendra, Muhammad (International Journal of Trends in Mathematics Education Research, 2023)
This research is motivated by the fact that not all students can do math calculations well. This can be seen when students carry out exercises on matrix material and the application of linear functions in economics that require numerical skills, namely the addition and subtraction of integers. There are still many students who are confused in doing the exercise, especially with quite large numbers such as tens and hundreds. At the time of doing the distribution of many students who hesitate in doing it. Likewise with multiplication, there are even some students who have not memorized multiplication from 1 to 10. From this the researcher concludes that not all students have good numerical skills, so that students in working on math problems tend to experience difficulties and cause students' low economic mathematics learning outcomes. The average student learning outcomes are still below the minimum standard, in this case it can be seen from the midterm exam scores in mathematics economics management students at the Faculty of Economics, Universitas Sumatera Barat. So, one of the factors that influence students' learning outcomes in economics mathematics is numerical ability. This type of research is ex post facto correlational research, namely research that is intended to determine whether there is a relationship between two or several variables. The population in this study were all management students at the Faculty of Economics, Universitas Sumatera Barat, who took four classes of economics mathematics, consisting of 128 students. The instruments used in this study were numerical ability tests and learning achievement tests. The analysis used in this research is linear correlation analysis. The results showed that there was a significant relationship between numerical ability and the learning outcomes of economic mathematics students at the Faculty of Economics, Universitas Sumatera Barat. This is also seen from the value of the correlation coefficient , the correlation coefficient when seen in the table of the level of closeness of the relationship between X and Y variables, then the level of closeness of the relationship is in the medium relationship category because it is in the range. So, it can be concluded that there is a significant relationship between numerical ability and the results of learning economics mathematics from students of management at the Faculty of Economics, Universitas Sumatera Barat.